Biomimetic, Programmable, and Part‐by‐Part Maneuverable Single‐Body Shape‐Morphing Film. (25th March 2023) - Jeong, Yongrok; Ahn, Junseong; Ha, Ji-Hwan; Ko, Jiwoo; Hwang, Soon-Hyoung; Jeon, Sohee; Bok, Munjeong; Jeong, Jun-Ho; Park, Inkyu
Abstract : Bio‐Inspired Shape Morphing Film In article number 2200293, Yongrok Jeong, Jun‐Ho Jeong, Inkyu Park, and co‐workers propose the fabrication method of the biomimetic, programmable, and part‐by‐part maneuverable single‐body shape morphing film (SMF) inspired by nature. The proposed SMF can realize various movements from nature such as the gripping motion of Drosera capensis and gait motion of the inchworm.